Considerações sobre um acaso na impressão xilográfica - Alves, André Magnago (2025)
Investigation into a chance event that occurred in a particular creation process that led to a technical, conceptual, and imaginative advance in woodcut language. It begins with background research that aims to attest to the plausibility of such an expansion of woodcut. The emergence of a fact, unprogrammed, within a predictable process generated internal contradictions that are associated with a faulty act and promote said progress. From the analysis of the report about the phenomenon discussed, the urgency for a subject model that was compatible is noted and was obtained from Nietzsche's critiques of the modern subject. The transit between conceptual poles linked to the Derridian concept of difference leads us to a dialectic between technical and conceptual surprises arising as traces of these transits between an already dominated area of knowledge that is surprised and antagonized with phenomena arising in artistic creation. In the end, the hypothesis of chance, in theory, can be explained by Michael Polanyi's theory as tacit knowledge, a knowledge of which the subject is not previously aware and through which he projects qualities onto the things he perceives